Altered Taste Function in Young Individuals With Type 1 Diabetes - Catamo, Eulalia; Robino, Antonietta; Tinti, Davide; Dovc, Klemen; Franceschi, Roberto; Giangreco, Manuela; Gasparini, Paolo; Barbi, Egidio; Cauvin, Vittoria; Rabbone, Ivana; Battelino, Tadej; Tornese, Gianluca (Frontiers in Nutrition, 2022)
Past studies on altered taste function in individuals with type 1 diabetes have yielded inconsistent results. We therefore evaluated taste recognition and possible association with personal and diseases characteristics in young individuals with type 1 diabetes and healthy controls. Taste recognition and intensity for 6-n-propylthiouracil (PROP), quinine, citric acid, sucrose, and sodium chloride were assessed using a filter paper method in 276 participants with type 1 diabetes and 147 healthy controls. Personal and clinical data were recorded for all participants during a baseline visit. Regression analysis was adjusted for sex, age, and standardized BMI. Overall, 47% of participants with type 1 diabetes versus 63.5% of healthy controls recognized all tastes (p=0.006). Moreover, a lower capacity for recognizing the bitter taste of PROP and the sour taste of citric acid was found in participants with type 1 diabetes compared to healthy controls (p=0.014 and p=0.003, respectively). While no significant effect of glycemic control on taste recognition was found, an association with lower age at onset emerged. Our findings suggest an impaired taste perception in individuals with type 1 diabetes, possibly linked to age at onset.